The Effect of Alkali Treatment ofOPKS Filler on Mechanical Property of Polyester-Composite - Nabinejad, O.; Debnath, Sujan; Rahman, Muhammad; Moola, Mohan; Liew, W.; Davies, Ian (Trans Tech Publications, Switzerland, 2014)
This paper presents a study on the effect of alkali treatment of Oil Palm Kernel Shell(OPKS) on the mechanical properties ofpolyester composite. The dosage of NaOH in this study islimited to 5wt% concentration.The experiments on mechanical properties investigate the tensilestrength, the flexural strength and theflextural modulus of untreated, cold alkali treated and hotalkali treated OPKS reinforced polyester composite. It is found that the alkali treatment improvesthe mechanical properties of the composite. However, the improvement due tothe hot alkalitreatment is significant compared to the cold alkali treatment. The morphology of OPKS and thefracture surface of OPKS composites were investigated using scanning electron microscopy (SEM),showing a rough surface and good interfacial adhesion between OPKS as filler and polyester as amatrix.